Analisis Daya Dukung Wisata Kota Lama untuk Pengembangan Wisata Budaya Kota Semarang - Shinta, Lukito Clara; Budi, Santoso Apik; Moch., Arifien (Geo-Image, 2019)
Tourism development in the Old City Semarang was conducted to prepare for the 2020 World Heritage from UNESCO. Based on this, the tourism potentials in the Old City Semarang need to be improved to attract tourists to come. As a tourism area, the harmony between the number of tourists with the provided capacity is indispensable for providing pleasure for the coming tourists. The aims of this study are 1. To identify the cultural tourism potential of Old City, 2. To calculate the support capacity of the Old City as a tourist destination in Semarang, and 3. To analyze the development of cultural tourism. The data analysis used is descriptive and the calculation of support capacity using the Douglas method (1975) in Fandeli (2001). Based on the results of the study, it found that the effective support capacity of the Dream Zone Museum was 96, the 3D & Trick Art Museum was 447, Art Contemporary Gallery was 5,997 and the Old City Park was 25. The results showed that the attractions in Old City Semarang have different support capacity. The Dream Zone Museum and the Old City Park are need to be developed because of the high support capability value. Whereas, the 3D & Trick Art Museum and Art Contemporary Gallery are included in the exceeded support capacity, so that there is a need of control and arrangement in the development.